Tratamento de resíduos agropecuários através do processo de vermicompostagem - Almeida, Gabriel Rockenbach de (2011)
A trial was conducted to evaluate earthworm composting as an alternative for treating a mixture of bovine manure, wood shavings and rice hull ash, in order to produce an organic fertilizer. The fertilizer might be sold, becoming an alternative income for dairy cattle producers and reducing the environmental impact of dairy cattle activity, turning it into an environmental friendly and economic activity. Earthworm composting took place in 20 wood boxes (0.40m x 0.50m x 0.30m). Each box received 300 earthworms (Eisenia andrei). A total of five treatments with four replications were studied: T1 (100% bovine manure); T2 (50% bovine manure + 25% wood shavings + 25% rice hull ash); T3 (33% bovine manure + 33% wood shavings + 33% rice hull ash); T4 (25% bovine manure + 50% wood shavings + 25% rice hull ash); and T5 (25% bovine manure + 25% wood shavings + 50% rice hull ash). A completely randomized design was used. ANOVA was used for data analysis and the averages were compared by Tukey test at 5%. Humus samples were collected at day 45 and at the end of trial (day 60). The following variables were studied: pH, dry matter, ash, organic matter, carbon, nitrogen, C/N ratio, phosphorus, calcium, potassium and magnesium. Earthworm composting of pure bovine manure is an effective alternative for treating such dairy cattle production residue. The produced humus contains physical and chemical properties which allow it to be used as an organic fertilizer. However, the mixture of wood shavings and rice hull ash does not produce a good quality fertilizer, according to the current Brazilian legislation.